2011
DOI: 10.1074/jbc.m110.201392
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Critical Residues in Gα13 for Stimulation of p115RhoGEF Activity and the Structure of the Gα13-p115RhoGEF Regulator of G Protein Signaling Homology (RH) Domain Complex

Abstract: RH-RhoGEFs are a family of guanine nucleotide exchange factors that contain a regulator of G protein signaling homology (RH) domain. The heterotrimeric G protein G␣ 13 stimulates the guanine nucleotide exchange factor (GEF) activity of RHRhoGEFs, leading to activation of RhoA. The mechanism by which G␣ 13 stimulates the GEF activity of RH-RhoGEFs, such as p115RhoGEF, has not yet been fully elucidated. Here, specific residues in G␣ 13 that mediate activation of p115RhoGEF are identified. Mutation of these resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Structural and biochemical experiments have established that GTP-bound Gα 12/13 subunits make direct contacts with the RH-domain, and that this interaction positively regulates RhoGEF activity. [34][35][36][37][38] It has also been shown that the RH domain of p115 and LARG also can function as negative regulator of Gα 12/13 by increasing its intrinsic hydrolysis rate of GTP to GDP. 33,37,39 While interactions of RH-RhoGEFs with Gα 12/13 is believed to be the primary and the most well-characterized mode of regulation, several reports also indicate that additional control could be provided by phosphorylation of tyrosine residues.…”
Section: Regulation Of Rhogefs By Tyrosine Phosphorylationmentioning
confidence: 99%
“…Structural and biochemical experiments have established that GTP-bound Gα 12/13 subunits make direct contacts with the RH-domain, and that this interaction positively regulates RhoGEF activity. [34][35][36][37][38] It has also been shown that the RH domain of p115 and LARG also can function as negative regulator of Gα 12/13 by increasing its intrinsic hydrolysis rate of GTP to GDP. 33,37,39 While interactions of RH-RhoGEFs with Gα 12/13 is believed to be the primary and the most well-characterized mode of regulation, several reports also indicate that additional control could be provided by phosphorylation of tyrosine residues.…”
Section: Regulation Of Rhogefs By Tyrosine Phosphorylationmentioning
confidence: 99%
“…In resting cells, RH-RhoGEFs are distributed throughout the cytoplasm of unstimulated cells and translocate to the PM upon activation of G␣ 12 or G␣ 13 subunits (19 -21). Direct activation of these RhoGEFs has been difficult to demonstrate in vitro with the exception of p115RhoGEF (22), suggesting that the dominant mechanism by which G␣ 12/13 subunits activate RHRhoGEFs is via membrane recruitment.…”
mentioning
confidence: 99%
“…6). Alignment is based upon the crystal structure of the RH domain of p115GEF (41,42). Despite low 32% sequence identities shared between the RH domains of p115RhoGEF and PDZRhoGEF, these domains share nearly identical three-dimensional structures, a root mean square deviation of 0.608 Å on C␣ values (41,42).…”
Section: Rgnef C-terminal Domain Immunoprecipitated With Activated G␣mentioning
confidence: 99%
“…Next, we aligned the C-terminal portion of Rgnef (entries P97433, Q8N1W1, and P0C6P5) to the RH domains of the p115RhoGEF family. Relying on this alignment, we constructed a computational model of the Rgnef RH-like domain bound to G␣ 13 using Modeler (40) based on the homology to the RH-like domain of ArhGEF11, for which the structure in complex with G␣ 13 (Protein Data Bank code 3CX8) is available (41,42). The molecular complex was refined using energy minimization with AMBER 12.0 employing the Amberff99SB-ILDN force field (43).…”
Section: G17amentioning
confidence: 99%